Knowledge managament strategy for application team in PT. CSP - Widanta Kristyo Adhy, Ignatius; Hidajat Tjakraatmadja, Jann (The Indonesian Journal of Business Administration, 2019)
Abstract - PT. CSP is a local business partner of PT. ERS in Indonesia, which engaged in the field of advanced and smart industrial technology in sensors, field instrumentation, and integrated process and safety automation control system. The automation product that become focus in this research is in DeV product which sold to its client under Solution and Control Division as sales division that faces a business challenge to increase the working efficiency in coordination and communication for submitting project proposal to meet customer expectation and increase the opportunity to win the project. The problem is low efficiency project proposals submission that can have an impact on reducing opportunities for selling and decreasing company profits, this is not good because it has an impact on the performance of the sales force and can result in layoffs. The research is using qualitative methods to identify the problems and adopts the Nonaka’s SECI model in knowledge transformation cycle and the Jann model knowledge management framework as the underlying theory and conceptual framework. The outcome of this research is to get knowledge and initiatives needed to close the gap with knowledge management implementation plan to solve the problem also to increase the efficiency to improve project submission proposal from 14 to 10 working days. Implementation plan cover the 3 enablers of knowledge management of people, process, and technology which every member shall adopt and continuously doing it in order to strengthen application engineer team.  Keywords: Knowledge Management, Jann Model, SECI Model, Sales Division, Application Engineer